2019
DOI: 10.3390/molecules24020368
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing Reveals the Role of Epigallocatechin-3-Gallate in Regulating Putative Novel and Known microRNAs Which Target the MAPK Pathway in Non-Small-Cell Lung Cancer A549 Cells

Abstract: Lung cancer constitutes 85% of non-small cell lung cancer diagnosed cases. MicroRNAs are novel biomarkers that are capable of modulating multiple oncogenic pathways. Epigallocatechin-3-gallate (EGCG) is a potent chemopreventive and chemotherapeutic agent for cancer. We aimed to identify important known and putative novel microRNAs modulated by EGCG in A549 cells using next-generation sequencing and identify their gene targets. Preliminary analysis revealed an IC50 value of 309 μM with G0/G1 phase arrest at 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 64 publications
0
30
0
Order By: Relevance
“…EGCG has been demonstrated to possess anticancer bioactivity, which has attracted attention; EGCG has demonstrated cancer preventive activity in various types of human cancer, including lung, oral cavity and esophageal cancers (37,38). Numerous studies have been conducted on the effects of EGCG on lung cancer (39)(40)(41)(42), and it had been reported that oral administration of EGCG was feasible and safe to patients with advanced lung cancer (43).…”
Section: Discussionmentioning
confidence: 99%
“…EGCG has been demonstrated to possess anticancer bioactivity, which has attracted attention; EGCG has demonstrated cancer preventive activity in various types of human cancer, including lung, oral cavity and esophageal cancers (37,38). Numerous studies have been conducted on the effects of EGCG on lung cancer (39)(40)(41)(42), and it had been reported that oral administration of EGCG was feasible and safe to patients with advanced lung cancer (43).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, FXS-3 could activate the JNK signaling pathway but inhibit the ERK/p38 signaling pathways, which might be an important mechanism underlying the apoptosis of lung cancer cells induced by FXS-3. Recently, microRNAs play a significant role in the MAPK signaling cascade [9]. It will be interesting to explore the potential microRNAs modulated by FXS-3 in A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies showed that lncRNAs are dysregulated after EGCG treatment in lung cancer, nasopharyngeal carcinoma, prostatic hyperplasia, osteoarthritis, etc [33][34][35] However, whether lncRNAs mediated the protective role of catechin, a kind of bioactive polyphenol that has a variety of pharmacological and biological properties and plays a protective role in MI/R injury, 14 against H/R-induced myocardial cell apoptosis or MI/R injury is largely unknown. For example, studies showed that lncRNAs are dysregulated after EGCG treatment in lung cancer, nasopharyngeal carcinoma, prostatic hyperplasia, osteoarthritis, etc [33][34][35] However, whether lncRNAs mediated the protective role of catechin, a kind of bioactive polyphenol that has a variety of pharmacological and biological properties and plays a protective role in MI/R injury, 14 against H/R-induced myocardial cell apoptosis or MI/R injury is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs are the cellular responding molecules for bioactive polyphenol treatment in various diseases. For example, studies showed that lncRNAs are dysregulated after EGCG treatment in lung cancer, nasopharyngeal carcinoma, prostatic hyperplasia, osteoarthritis, etc [33][34][35] However, whether lncRNAs mediated the protective role of catechin, a kind of bioactive polyphenol that has a variety of pharmacological and biological properties and plays a protective role in MI/R injury, 14 against H/R-induced myocardial cell apoptosis or MI/R injury is largely unknown. In this study, we found that lncRNA MIAT expression was down-regulated after catechin treatment in myocardial Same as the transcriptional regulation of other genes, mounting evidence showed that the transcription of lncRNAs could be regulated by transcription factors at the transcriptional level under physiological and pathological conditions.…”
Section: Discussionmentioning
confidence: 99%